THE APPLICATION OF THE THINK-PAIR-SHARE (TPS) COOPERATIVE LEARNING MODEL TO ENHANCE STUDENTS' LEARNING OUTCOMES IN ECONOMICS AT SMA NEGERI 1 DARUL IMARAH, ACEH BESAR - JULIA RAHMI (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study investigates the application of the Think-Pair-Share (TPS) cooperative learning model to enhance students' learning outcomes in Economics at SMA Negeri 1 Darul Imarah, Aceh Besar. Recognizing the significance of Economics as a core subject that equips students with critical knowledge about financial systems, market behaviors, and socio-economic issues, this research addresses the observed challenges in student engagement and academic achievement. The TPS model encourages active participation by fostering individual thinking, collaborative dialogue, and collective sharing, promoting a deeper understanding of complex concepts. Utilizing a quasi-experimental design, the study involved two classes: an experimental group that implemented the TPS model and a control group that followed traditional teaching methods. Data were collected through pre-tests and post-tests, coupled with student surveys to assess their engagement levels and perceptions of the learning process. The analysis revealed significant differences in academic performance between the two groups, with the experimental group demonstrating noticeable improvement in their understanding of Economic principles. Furthermore, qualitative feedback from the students indicated increased motivation and collaborative learning experiences, underscoring the effectiveness of the TPS model in fostering a supportive learning environment. The findings contribute to the existing body of literature on cooperative learning strategies and offer practical implications for educators seeking to enhance instructional quality and student engagement in Economics. Ultimately, this study underscores the importance of innovative teaching methodologies in fostering academic success and preparing students for informed participation in the socio-economic landscape of their communities.